2008
DOI: 10.1016/j.bbamem.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Lipid organization in human and porcine stratum corneum differs widely, while lipid mixtures with porcine ceramides model human stratum corneum lipid organization very closely

Abstract: The conformational disordering and lateral packing of lipids in porcine and human isolated stratum corneum (SC) was compared using Fourier transform infrared spectroscopy (FTIR). It was shown that SC of both species differ markedly, porcine SC lipids being arranged predominantly in a hexagonal lattice while lipids in human SC are predominantly packed in the denser orthorhombic lattice. However, the lipid organization of equimolar ceramide:cholesterol:free fatty acid (CER:CHOL:FFA) mixtures prepared with isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 46 publications
4
55
0
Order By: Relevance
“…Depending on their chain lengths and headgroup architectures, the ceramides and the free fatty acids may participate in the same or in separate OR lattices [34]. Reduction of the content of free fatty acids, shortening the chain lengths of both ceramides and fatty acids and mismatch between the lipid chain lengths inhibit the formation of OR [19,33,76,92,93]. Ceramide EOS was found to stabilize the OR phases [94].…”
Section: Lateral Organizationmentioning
confidence: 99%
“…Depending on their chain lengths and headgroup architectures, the ceramides and the free fatty acids may participate in the same or in separate OR lattices [34]. Reduction of the content of free fatty acids, shortening the chain lengths of both ceramides and fatty acids and mismatch between the lipid chain lengths inhibit the formation of OR [19,33,76,92,93]. Ceramide EOS was found to stabilize the OR phases [94].…”
Section: Lateral Organizationmentioning
confidence: 99%
“…Optimum percentages of all three major classes of SC lipid are important for the formation of orthorhombic lateral packing [4,6,8,19,20,22,39,48,52,53]. A study by Norlén et al [27] indicated that as one goes deeper into the SC layers, the amount of FFA decreases, which results in an increase in transepidermal water loss (TEWL).…”
Section: Stratum Corneummentioning
confidence: 99%
“…The architecture of the CER head group also affects the lateral packing of the lipids. The head groups of the phytosphingosine-based CERs, such as CER[AP], have the highest number of hydroxyl groups, which enhances the formation of hydrogen bonds in the head group region and increases the stability of the orthorhombic phase [53,54]. Long-chain FFAs have stronger van der Waals interactions, promoting the orthorhombic lateral packing [4,10,53].…”
Section: Stratum Corneummentioning
confidence: 99%
See 1 more Smart Citation
“…Meyer et al 1978Meyer et al , 2003Meyer et al , 2007Meyer 1986). Because although in the domesticated pig stratum corneum lipids are arranged predominantly in a hexagonal lattice while lipids in the human corneal layer system are predominantly packed in the denser orthorhombic lattice, porcine ceramides model human stratum corneum lipid organisation very closely (Caussin et al 2008).…”
Section: Discussionmentioning
confidence: 99%